The indemnity bond in the change of a subagent into a main agent - Lara González, Rafael (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
Article 17(2)(a) of Council Directive 86/653/EEC of 18 December 1986 on the coordination of the laws of the Member States relating to self-employed commercial agents, must be interpreted as meaning that the goodwill indemnity which has been paid by the principal to the main agent in respect of the customer base brought by the subagent is capable of constituting, for the main agent, a substantial benefit. However, the payment of a goodwill indemnity to the subagent may be regarded as not being equitable, within the meaning of that provision, where the subagent continues his or her commercial agency business in relation to the same clients and for the same products but in the context of a direct relationship with the main principal, which replaced the main agent that had previously engaged him or her.
Keywords: Goodwill indemnity; main agent; substantial benefit; subagent; equitable